PENGARUH PAYLATER DAN SELF CONTROL TERHADAP PERILAKU IMPULSIVE BUYING PADA GENERASI Z PENGGUNA E-COMMERCE DI KABUPATEN TASIKMALAYA - Latipah Amaliah; Dheri Febiyani Lestari (JIM : Journal Of International Management, 2026)
The purpose of this scientific study is to determine the impact of paylater use and self-control on impulsive buying in Generation Z e-commerce users in Tasikmalaya Regency. The research method used is associative quantitative. Sampling was carried out using non-probability sampling techniques through purposive sampling, selecting participants based on certain criteria, with multiple linear regression analysis as the main tool. The results of this research reveal that: (1) paylater and self-control have a positive and significant influence on impulsive buying behavior, (2) Paylater positively and significantly influences impulsive buying behavior, and (3) Self-control positively and significantly influences impulsive buying behavior. This emphasizes that the ease of access to digital payments and the level of individual self-control in forming excessive consumer habits in Generation Z in Tasikmalaya Regency.